Coated steel sheet with excellent strength, formability and surface quality and manufacturing method thereof
Patent Information
- Application Number
- JP2023529070
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-11-18
- Filing Date
- 2021-11-10
- Publication Date
- 2025-03-12
- Estimated Expiration
- 2041-11-10
AI Technical Summary
【0014】 本発明の一側面によると、高い実収率を確保しながらも、表面外観に優れるとともに、高強度及び高成形性を有するめっき鋼板及びその製造方法を提供することができる。
Smart Images

Figure 0007644816000007 
Figure 0007644816000008 
Figure 0007644816000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a plated steel sheet excellent in strength, formability and surface quality that can realize weight reduction of automobiles, and a manufacturing method thereof. More specifically, the present invention relates to a zinc-based plated steel sheet having high strength and high formability that can be suitably used as a material for exterior panels of automobiles, and a manufacturing method thereof. [Background technology]
[0002] Cold-rolled steel sheets processed by press working or the like are used as exterior panels for automobiles, and generally require high formability. In recent years, in order to prevent global warming, new targets for improving automobile fuel efficiency have been set as carbon dioxide emission control measures, and preferential tax systems have been introduced for fuel-efficient automobiles, so that automobile fuel efficiency needs to be improved. Reducing the weight of automobile bodies is an effective means for improving automobile fuel efficiency, and from the viewpoint of weight reduction, slimming of steel sheets for automobile bodies has been required. However, recently, an increasing number of automobile manufacturers are trying to reduce costs by realizing weight reduction and shortening processes by eliminating reinforcing parts using high strength, even if the thickness is thick.
[0003] There is a demand for zinc-based plated high tensile steel sheets that satisfy the requirements for high strength steel sheets and have excellent surface appearance and good press formability as steel sheets for automobile bodies which are pressed into complex shapes.
[0004] On the other hand, in the case of high tensile steel sheets for automobiles, a method is carried out in which solid solution strengthening elements such as Si, Mn, and P are contained in the steel in order to improve the strength of the steel sheet.
[0005] In particular, P is added to steel to increase the strength of the steel sheet, but P is an element that is very susceptible to segregation, and P segregated on the surface of a slab is stretched in the longitudinal direction of the steel sheet by hot rolling and cold rolling, forming P segregation on the surface of a coil. In such P segregation, alloying is delayed during plating, which causes linear defects in the galvannealed steel sheet. To address this problem, a method has been proposed for manufacturing a galvannealed steel sheet using a steel sheet having a P content of 0.03% or more as a substrate, in which the steel sheet surface is ground with a grinding amount corresponding to the P content in the steel to eliminate non-uniformity on the steel sheet surface, and the alloying process is performed in an induction heating type alloying furnace (Patent Document 1).
[0006] In such conventional technology, in order to prevent linear defects in galvannealed steel sheets, for example, when using ultra-low carbon Ti-added steel sheets with a P content of 0.03% or more, the surface is scarfed (surface cut) by 3 mm or more at the continuous casting stage, and the surface is ground by 5 μm or more at the steel sheet stage before plating. This prevents the occurrence of shape defects after plating and ensures surface quality, but it is understood to be a cause of reduced yield. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Publication No. 2004-169160 Summary of the Invention [Problem to be solved by the invention]
[0008] An object of one aspect of the present invention is to provide a plated steel sheet that has excellent surface appearance, high strength and high formability while ensuring a high recovery rate, and a manufacturing method thereof.
[0009] The object of the present invention is not limited to the above. Anyone having ordinary knowledge in the technical field to which the present invention pertains will have no difficulty in understanding further object of the present invention from the entire contents of the specification of the present invention. [Means for solving the problem]
[0010] One aspect of the present invention is a steel sheet comprising: A plating layer formed on the base steel, The base steel contains, by weight, C: 0.003-0.009%, Si: 0.05% or less, Mn: 0.4-1.0%, P: 0.04-0.09%, S: 0.01% or less, N: 0.005% or less, S.Al: 0.1% or less, Mo: 0.03-0.08%, Ti: 0.005-0.03%, Nb: 0.02-0.045%, Cu: 0.06-0.15%, B: 0.003% or less, the balance being Fe and other unavoidable impurities. A plated steel sheet is provided that satisfies the following relational expression 1.
[0011] [Equation 1] 1.6≦Mt / Ms≦6 (In the above Relational Formula 1, Mt represents the average Mo content by weight at a point 0.1 μm away from the surface of the base iron in the thickness direction of the base iron side. Ms represents the average Mo content by weight at a point 1 / 4t away from the surface of the base iron in the thickness direction of the base iron side. t represents the total average thickness of the base iron and is in the range of 0.8 to 1 mm.)
[0012] Further, another aspect of the present invention is a step of continuously casting a steel containing, by weight percent, C: 0.003-0.009%, Si: 0.05% or less, Mn: 0.4-1.0%, P: 0.04-0.09%, S: 0.01% or less, N: 0.005% or less, S.Al: 0.1% or less, Mo: 0.03-0.08%, Ti: 0.005-0.03%, Nb: 0.02-0.045%, Cu: 0.06-0.15%, B: 0.003% or less, the balance being Fe and other unavoidable impurities; reheating the slab obtained by the continuous casting; hot rolling the reheated slab to provide a hot rolled steel sheet; coiling the hot-rolled steel sheet; cold rolling the hot rolled steel sheet to obtain a cold rolled steel sheet; Annealing the cold rolled steel sheet; The method includes immersing the annealed cold-rolled steel sheet in a zinc-based plating bath to perform hot-dip galvanizing, The above-mentioned continuous casting provides a method for producing a plated steel sheet that satisfies the following relational expression 3.
[0013] [Equation 3] 1≦Vc≦5-[P] / [Mo] (In the above Relational Formula 3, Vc represents the average casting speed during continuous casting, and is expressed in m / min. [P] represents the average P content in the slab in weight percent, and [Mo] represents the average Mo content in the slab in weight percent.) Effect of the Invention
[0014] According to one aspect of the present invention, it is possible to provide a plated steel sheet that has excellent surface appearance, high strength and high formability while ensuring a high recovery rate, and a manufacturing method thereof.
[0015] The various and beneficial advantages and effects of the present invention are not limited to the above-mentioned contents, but can be more easily understood in the course of describing specific embodiments of the present invention. [Brief description of the drawings]
[0016] [Figure 1] 1 shows a photograph of the surface of the plated steel sheet produced in Example 1 of the present invention, observed with a scanning electron microscope (SEM). [Diagram 2] 1 shows a photograph of the surface of a plated steel sheet produced in Comparative Example 4 of the present invention, observed with a scanning electron microscope (SEM). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Hereinafter, preferred embodiments of the present invention will be described. However, the embodiments of the present invention can be modified into various other forms, and the scope of the present invention is not limited to the embodiments described below. Furthermore, the embodiments of the present invention are provided to more completely explain the present invention to those having average knowledge in the art.
[0018] As described above, in the conventional technology, in order to prevent linear defects in plated steel sheets and ensure surface quality, it was necessary to perform a scarfing (surface cutting) treatment on the surface at the continuous casting stage and further a grinding treatment on the surface at the steel sheet stage before plating, which caused a decrease in recovery rate.
[0019] Therefore, the present inventors conducted extensive research to solve the problems of the prior art, and as a result, found that by adding appropriate amounts of titanium (Ti) and / or niobium (Nb), which are strong carbonitride forming elements, to steel, formability can be ensured by minimizing solid solution elements such as carbon (C), nitrogen (N) and sulfur (S).The present inventors also found that, in addition to the above, by adding appropriate amounts of phosphorus (P) and molybdenum (Mo), etc. to steel, a high-strength, highly formable plated steel sheet for vehicle exterior panels having excellent surface quality while having a tensile strength of 390 MPa or more can be manufactured, and thus completed the present invention.
[0020] Hereinafter, the plated steel sheet having excellent surface quality, high strength and high formability, which can be preferably used as a raw material for automotive exterior panels, and the manufacturing method thereof will be described. In this regard, the plated steel sheet for automotive exterior panels must satisfy press formability such as deep drawability as well as high tensile strength.
[0021] The descaled rolled steel sheet that serves as the base material (base steel) of the plated steel sheet in this embodiment is a high-tensile steel sheet whose basic component is ultra-low carbon steel to improve workability, with appropriate amounts of strengthening elements such as Mn and P added.
[0022] That is, a plated steel sheet according to one aspect of the present invention includes a base iron and a plating layer formed on the base iron. The base iron includes, by weight percent, C: 0.003-0.009%, Si: 0.05% or less, Mn: 0.4-1.0%, P: 0.04-0.09%, S: 0.01% or less, N: 0.005% or less, S.Al: 0.1% or less, Mo: 0.03-0.07%, Ti: 0.005-0.03%, Nb: 0.02-0.045%, Cu: 0.06-0.15%, B: 0.003% or less, the balance being Fe and other inevitable impurities. The reasons for adding the basic component elements of the base iron and the reasons for limiting the contents thereof will be specifically described below.
[0023] Carbon (C): 0.003~0.009% C is an interstitial solute element and has a significant effect on the formation of the texture of the steel sheet during cold rolling and annealing. When the amount of solute carbon in steel is large, the growth of crystal grains having a {111} gamma (γ)-fiber texture, which is advantageous for drawing, is suppressed, and the growth of crystal grains having {110} and {100} textures is promoted, resulting in a decrease in the drawability of the annealed sheet. Furthermore, when the C content exceeds 0.009%, the contents of Ti and Nb required for precipitating C as carbides become large, which is not only disadvantageous from the viewpoint of economy, but also may cause the formation of pearlite and the like, resulting in a decrease in formability. Therefore, it is preferable to limit the C content to 0.009% or less. Furthermore, when the C content is less than 0.003%, a problem may occur in which sufficient strength cannot be ensured, so it is preferable to limit the C content to 0.003% or more. On the other hand, more preferably, the lower limit of the C content may be 0.0038%, or the upper limit of the C content may be 0.008%.
[0024] Silicon (Si): 0.05% or less (excluding 0%) Silicon is an element that contributes to increasing strength through solid solution strengthening. In order to achieve the effect of increasing strength through solid solution strengthening, silicon must be added, and therefore the silicon content in the base steel is limited to more than 0%. However, if the silicon content exceeds 0.05%, there is a problem that surface scale defects are induced and the surface characteristics of the plating are deteriorated. Therefore, in the present invention, the silicon content is controlled to 0.05% or less. On the other hand, more preferably, the lower limit of the silicon content may be 0.024%, or the upper limit of the silicon content may be 0.042%.
[0025] Manganese (Mn): 0.4-1.0% Mn is a solid solution strengthening element that not only contributes to increasing strength but also plays a role in precipitating S in steel as MnS. If the Mn content is less than 0.4%, there is a concern of a decrease in strength, whereas if it exceeds 1.0%, there is a possibility of surface problems due to oxides, so the Mn content is preferably limited to 0.4 to 1.0%. On the other hand, more preferably, the lower limit of the Mn content may be 0.48%, or the upper limit of the Mn content may be 0.67%.
[0026] Phosphorus (P): 0.04-0.09% P has the best solid solution effect and is the most effective element for ensuring the strength of steel without significantly impairing the drawability. If the P content is less than 0.04%, it is impossible to ensure the desired strength, whereas if it exceeds 0.09%, secondary embrittlement and surface linear defects may occur due to P segregation. Therefore, it is preferable to limit the P content to 0.04 to 0.09%. On the other hand, more preferably, the lower limit of the P content may be 0.048%, or the upper limit of the P content may be 0.089%.
[0027] Molybdenum (Mo): 0.03-0.08% Mo is an element with high affinity for P (phosphorus) and plays a role in suppressing P segregation. In order to ensure high strength in ultra-low carbon steel, P must be used unavoidably, but proper addition of Mo can partially contribute to improving surface defects caused by P segregation. If the Mo content is less than 0.03%, there is no significant effect on the intended surface improvement. If the Mo content exceeds 0.08%, the price increases and the cost competitiveness decreases, so the Mo content is preferably limited to 0.03 to 0.08%. On the other hand, more preferably, the lower limit of the Mo content may be 0.05%, or the upper limit of the Mo content may be 0.078%.
[0028] Sulfur (S): 0.01% or less (excluding 0%), Nitrogen (N): 0.005% or less (excluding 0%) S and N are impurities present in steel and are inevitably added, so that the S and N contents in the base steel each independently exceed 0%. However, in order to ensure excellent welding properties, it is preferable to control the contents as low as possible. Therefore, the S content is controlled to 0.01% or less, and the N content is controlled to 0.005% or less. On the other hand, more preferably, the lower limit of the S content may be 0.0015%, or the upper limit of the S content may be 0.0034%. Also, more preferably, the lower limit of the N content may be 0.0008%, or the upper limit of the N content may be 0.004%.
[0029] Aluminum (Al): 0.1% or less (excluding 0%) Al precipitates AlN and contributes to improving the drawability and ductility of steel. In order to achieve the effect of improving the drawability and ductility, the Al content in the base steel is greater than 0%. However, if the Al content exceeds 0.1%, there is a problem that internal defects occur in the steel sheet due to excessive formation of Al inclusions during steelmaking operations, so it is preferable to control the Al content to 0.1% or less. On the other hand, more preferably, the lower limit of the Al content may be 0.025%, or the upper limit of the Al content may be 0.08%.
[0030] Titanium (Ti): 0.005 to 0.03% Ti is an element that reacts with solute carbon and solute nitrogen during hot rolling to precipitate Ti-based carbonitrides, thereby greatly contributing to improving the drawability of the steel sheet. If the Ti content is less than 0.005%, carbonitrides cannot be sufficiently precipitated, resulting in poor drawability. On the other hand, if the Ti content exceeds 0.03%, it is difficult to control inclusions during steelmaking operations, and inclusion defects may occur, so it is preferable to limit the Ti content to 0.005 to 0.03%. On the other hand, more preferably, the lower limit of the Ti content may be 0.007%, or the upper limit of the Ti content may be 0.012%.
[0031] Niobium (Nb): 0.02-0.045% Nb is the most effective element for producing very fine grains by the rolling and cooling process when the non-recrystallized region of the austenite region due to the hot rolling solute drag and precipitate pinning effect spreads to the high temperature region. If the Nb content is less than 0.02%, the range of the non-recrystallized temperature of the austenite in the steel narrows, and the effect of refining the grain size is small. On the other hand, if it exceeds 0.045%, there is a problem that the high temperature strength increases and hot rolling becomes difficult, so the Nb content is preferably limited to 0.02 to 0.045%. On the other hand, more preferably, the lower limit of the Nb content may be 0.028%, or the upper limit of the Nb content may be 0.044%.
[0032] Boron (B): 0.003% or less (excluding 0%) B is an element added to steel to prevent secondary work embrittlement caused by the addition of P, and in order to achieve the effect of preventing secondary work embrittlement, the B content in the base steel exceeds 0%. However, if the B content exceeds 0.003%, the ductility of the steel sheet decreases, so the B content is preferably limited to 0.003% or less. On the other hand, more preferably, the lower limit of the B content may be 0.0004%, or the upper limit of the B content may be 0.0015%.
[0033] Copper (Cu): 0.04-0.15% Cu is an element added to ensure strength, and is difficult to remove when adjusting the composition of steel by steelmaking. Therefore, it is preferable to add 0.04% or more of Cu to ensure strength, but if the Cu content exceeds 0.15%, it leads to grain boundary embrittlement and increased costs, so the Cu content is limited to 0.15% or less. On the other hand, more preferably, the lower limit of the Cu content may be 0.069%, and the upper limit of the Cu content may be 0.10%.
[0034] The remaining components include Fe and inevitable impurities. The addition of effective components other than the above composition is not excluded. On the other hand, the above inevitable impurities may include any impurities that may be unintentionally mixed in during a normal manufacturing process of plated steel sheets. Since a person skilled in the art can easily understand the meaning, there is no particular limitation thereto.
[0035] By satisfying the above-mentioned component system, the present invention can effectively provide a high-strength, extra-low carbon galvannealed steel sheet for automobile exterior panels having excellent formability.
[0036] That is, the present invention relates to a galvannealed steel sheet having an extremely low carbon steel as a basic component for improving formability and a high tensile steel sheet containing P as a strengthening element as a substrate (base iron), and the present invention can effectively prevent linear defects appearing due to segregation by appropriately adjusting the composition and alloying degree and containing the above-mentioned P. As a result, it is possible to effectively provide a galvannealed steel sheet that is applicable to automotive exterior panel materials and has an excellent surface appearance, and a manufacturing method thereof.
[0037] Meanwhile, according to one aspect of the present invention, the base iron corresponds to an ultra-low carbon steel having a C content of 0.01% or less, and therefore the base iron may have a ferrite-based microstructure. In this case, the ferrite-based microstructure may include other structures that are inevitably generated.
[0038] Specifically, according to one aspect of the present invention, the microstructure of the base iron can contain, in terms of area fraction, 95% or more of ferrite, with trace amounts of remaining pearlite, etc. Alternatively, more preferably, the microstructure of the base iron can contain, in terms of area fraction, 99% or more of ferrite and 1% or less of pearlite, and most preferably, the microstructure of the base iron can be a single phase of ferrite (containing 100% ferrite).
[0039] By satisfying the above-mentioned microstructural characteristics, excellent formability can be ensured. That is, if the content of fine structures such as pearlite in the base steel exceeds 5%, there is a possibility that a problem of poor formability may occur.
[0040] According to one aspect of the present invention, in the base iron, the average grain size of the ferrite may be in the range of 5 to 15 μm (i.e., 5 μm or more and 15 μm or less), although this is not particularly limited. If the average grain size of the ferrite is less than 5 μm, the strength may be too high and the elongation rate may not be sufficiently ensured. If the average grain size of the ferrite exceeds 15 μm, the desired strength may not be ensured. On the other hand, although this is not particularly limited, from the viewpoint of further improving the above-mentioned effect, preferably, the lower limit of the average grain size of the ferrite may be 7 μm, or the upper limit of the average grain size of the ferrite may be 10 μm.
[0041] Here, the average grain size of ferrite refers to the average value of the circle equivalent diameters of the grains measured on a cut surface in the thickness direction of the plated steel sheet (i.e., the direction perpendicular to the rolling direction). More specifically, it refers to the average value of the measured grain size when a spherical grain is assumed to have a grain size that is the longest length penetrating the inside of the grain.
[0042] On the other hand, the plated steel sheet according to the present invention preferably satisfies the following relational expression 1.
[0043] [Equation 1] 1.6≦Mt / Ms≦6 (In the above Relational Formula 1, Mt represents the average Mo content by weight at a point 0.1 μm away from the surface of the base iron in the thickness direction of the base iron side. Ms represents the average Mo content by weight at a point 1 / 4t away from the surface of the base iron in the thickness direction of the base iron side. t represents the total average thickness of the base iron and is in the range of 0.8 to 1 mm.)
[0044] If the Mt / Ms value is less than 1.6, a problem may occur in that linear defects occur on the surface, and if the Mt / Ms value exceeds 6, a problem may occur in that the desired strength and elongation cannot be ensured. On the other hand, although not particularly limited, from the viewpoint of further improving the above-mentioned effects, preferably, the lower limit of the Mt / Ms value may be 1.9, or the upper limit of the Mt / Ms value may be 4.9.
[0045] In other words, as a result of extensive research, the inventors have found that by controlling the ratio of the Mo content in the extreme surface layer portion of the base iron (a point 0.1 μm away from the surface of the base iron in the thickness direction toward the center of the base iron) to the Mo content in the surface layer portion of the base iron (a point 1 / 4t away from the surface of the base iron in the thickness direction toward the center of the base iron) within an appropriate range, a plated steel sheet with excellent surface quality and high strength that is suitable for use as an automobile exterior panel material can be obtained.
[0046] Therefore, by satisfying the above-mentioned Relational Expression 1, it becomes possible to expand the application range of the high-strength cold-rolled steel sheet containing P to automobile bodies to a range that has not been applied before (for example, to the side outer, etc.), and as a result, it becomes possible to realize further weight reduction of the automobile body.
[0047] On the other hand, according to one aspect of the present invention, the plating layer may be a zinc plating layer or a zinc alloy plating layer. Although not particularly limited, the plating layer may have a composition containing, in weight %, Fe: 8 to 13%, the remainder Zn and other inevitable impurities, and by satisfying this, excellent plating effects such as powdering properties can be ensured. In this case, the Fe content is the mass percentage of Fe in the plating layer relative to the entire plating layer, and refers to the average Fe mass% content. The Fe content in the plating layer can be measured, for example, by dissolving the alloyed hot-dip galvanized layer in hydrochloric acid as an inhibitor and measuring it using ICP (Indectively Coupled Plasma) emission spectroscopy. If the Fe content in the plating layer is less than 8%, the Fe-Zn alloy phase is not sufficiently generated and a soft η-Zn phase remains on the surface layer of the plating, which may adversely affect the processability and adhesion. Furthermore, if the Fe content in the coating layer exceeds 13%, an excessively thick, hard and weak Fe-Zn alloy phase (e.g., Γ phase or Γ1 phase) is formed at the interface between the coating layer and the base steel, which may cause problems since it increases the brittleness of the interface between the coating layer and the base steel.
[0048] Although not particularly limited, according to one aspect of the present invention, the plated steel sheet can satisfy the following Relational Expression 2. The inventors have further found that ensuring surface appearance is closely influenced by the relationship between the P and Mo contents. That is, by satisfying the above Relational Expression 2, a plated steel sheet with excellent surface appearance can be effectively provided.
[0049] [Equation 2] [P] / [Mo]≦1.162 (In the above Relational Formula 2, the above [P] represents the average P content in weight percent in the base iron, and the above [Mo] represents the average Mo content in weight percent in the base iron.)
[0050] According to one aspect of the present invention, the tensile strength of the plated steel sheet may be 390 MPa or more, and preferably in the range of 390 to 490 MPa. When the tensile strength of the plated steel sheet is 390 MPa or more (or 690 MPa or more and 490 MPa or less), it is possible to realize weight reduction of automobiles using high tensile steel. On the other hand, more preferably, the lower limit of the tensile strength of the plated steel sheet may be 400 MPa, or the upper limit of the tensile strength of the plated steel sheet may be 480 MPa.
[0051] According to one aspect of the present invention, the plated steel sheet may have a yield strength of 205 MPa or more, and more preferably in the range of 205 to 350 MPa. If the yield strength of the plated steel sheet is too low, a problem may occur in that surface defects such as dents occur when the plated steel sheet is used as an outer panel of a vehicle, whereas if the yield strength is too high, a problem may occur in that formability is deteriorated.
[0052] According to one aspect of the present invention, the elongation of the plated steel sheet may be 28% or more, more preferably in the range of 28 to 43%, and most preferably in the range of 28 to 38%. When the elongation of the plated steel sheet satisfies the above range, excellent formability and processability can be ensured.
[0053] Next, a method for producing a plated steel sheet will be described in detail, although it is not meant that the plated steel sheet of the present invention should necessarily be produced by the following production method.
[0054] Yet another aspect of the present invention is a steel sheet comprising, by weight percent, 0.003 to 0.009% C, 0.05% or less Si, 0.4 to 1.0% Mn, 0.04 to 0.09% P, 0.01% or less S, 0.005% or less N, 0.1% or less S.Al, 0.03 to 0.08% Mo, 0.005 to 0.03% Ti, 0.02 to 0.045% Nb, 0.06 to 0.15% Cu, 0.003% or less B, the balance being Fe and other impurities. The present invention provides a method for producing a plated steel sheet, the method including the steps of continuously casting steel containing unavoidable impurities, reheating a slab obtained by the continuous casting, hot rolling the reheated slab to provide a hot rolled steel sheet, coiling the hot rolled steel sheet, cold rolling the hot rolled steel sheet to provide a cold rolled steel sheet, annealing the cold rolled steel sheet, and immersing the annealed cold rolled steel sheet in a zinc plating bath to perform hot-dip galvanization.
[0055] Meanwhile, the present inventors have conducted further research and confirmed that in order to provide a plated steel sheet which has excellent surface appearance, high strength and high formability while ensuring a high recovery rate, it is important to appropriately control the continuous casting speed in accordance with the concentration levels of P and Mo in the slab during continuous casting.
[0056] That is, according to one aspect of the present invention, the above-mentioned method for producing a plated steel sheet preferably satisfies the following Relational Expression 3 during continuous casting. Since the following Relational Expression 3 is an empirically obtained value, no particular units need to be determined, and it is sufficient that the following units of Vc (m / min) and [P] and [Mo] (wt%) are satisfied.
[0057] [Equation 3] 1≦Vc≦5-[P] / [Mo] (In the above Relational Formula 3, Vc represents the average casting speed during continuous casting, and is expressed in m / min. [P] represents the average P content in the slab in weight percent, and [Mo] represents the average Mo content in the slab in weight percent.)
[0058] In the present invention, if the average casting speed (Vc) during the continuous casting is less than 1 m / min, the surface P segregation cannot be sufficiently controlled, and surface defects may occur in the final material. Also, if the average casting speed (Vc) during the continuous casting exceeds the value of 5-[P] / [Mo], surface linear defects may occur, and the surface quality may deteriorate. This is interpreted as being due to the fact that the cooling rate of the slab is non-uniform due to the increase in the casting speed, and the thermal deformation of the slab surface accompanying cooling and the amount of NbC precipitated near the surface layer become non-uniform, which increases the cracking sensitivity of the surface, resulting in poor surface quality.
[0059] According to one aspect of the present invention, the continuous casting may be performed with a cooling water amount of 0.80 to 3.0 L / kg (more preferably, 0.80 to 1.91 L / kg), although this is not particularly limited. If the amount of cooling water is less than 0.80 L / kg during the continuous casting, the cooling rate of the slab surface is likely to be non-uniform, which may cause thermal deformation of the slab surface and non-uniform amounts of Ti-Nb composite precipitated near the surface, leading to increased sensitivity to surface cracking, which may cause surface defects. If the amount of cooling water exceeds 3.0 L / kg, solidification may occur rapidly, which may cause problems such as cracks on the continuously cast surface.
[0060] Meanwhile, according to one aspect of the present invention, the step of reheating the slab may be performed in the range of 1180 to 1230° C. If the reheating temperature of the slab is less than 1180° C., a production problem may occur due to a rolling load in the FM section, and if the reheating temperature of the slab is more than 1230° C., surface scale defects may occur.
[0061] According to one aspect of the present invention, the hot rolling can be performed so that the finish rolling temperature is Ar3 or higher, and more specifically, can be performed in the range of 880 to 970°C. If the hot rolling is performed at a temperature lower than 880°C, the steel is cooled below the Ar3 temperature, i.e., in the two-phase region, and coarse grains are generated in the surface layer, the grain size of the surface layer is nonuniform, and there is a possibility that a problem will occur in the final clarity. If the hot rolling is performed at a temperature higher than 970°C, there is a possibility that a problem will occur in that the grain size is not sufficiently fine and the final material is insufficient. On the other hand, although not particularly limited, from the viewpoint of further improving the above-mentioned effects, preferably, the lower limit of the finish rolling temperature may be 915°C, or the upper limit of the finish rolling temperature may be 940°C.
[0062] According to one aspect of the present invention, the coiling step of the hot-rolled steel sheet may be performed at 600 to 640°C. If the coiling temperature is less than 600°C, precipitates such as Ti(Nb)C are not sufficiently generated, and the amount of solute carbon increases, which may affect behavior such as recrystallization and particle growth during annealing, and may cause problems in ensuring the desired strength and elongation. If the coiling temperature exceeds 640°C, a problem may occur in that the surface is deteriorated due to the generation of secondary scale. On the other hand, although not particularly limited, from the viewpoint of further improving the above-mentioned effects, preferably, the lower limit of the coiling temperature may be 612°C, or the upper limit of the coiling temperature may be 635°C.
[0063] According to one aspect of the present invention, the hot-rolled steel sheet is subjected to a pickling process for removing surface scale, and then cold-rolled at a rolling reduction of 70 to 83% to obtain a cold-rolled steel sheet. If the rolling reduction during the cold rolling is less than 70%, the {111} texture does not grow sufficiently, and therefore a problem of poor formability may occur. On the other hand, if the rolling reduction during the cold rolling is more than 83%, the load on the rolling roll during on-site production is very large, and the shape is deteriorated, and therefore a problem may occur. On the other hand, although not particularly limited, from the viewpoint of further improving the above-mentioned effects, preferably, the lower limit of the rolling reduction during the cold rolling may be 71%, or the upper limit of the rolling reduction during the cold rolling may be 77%.
[0064] According to one aspect of the present invention, the step of annealing the cold-rolled steel sheet may be performed at a temperature equal to or higher than the recrystallization temperature in the range of 740 to 830°C. By annealing at a temperature equal to or higher than the recrystallization temperature, deformation caused by rolling is removed, and the steel sheet is softened to improve workability. That is, if the annealing temperature is less than 740°C, ferrite recrystallization may not be completed, and a problem of insufficient elongation due to ultra-high strength may occur. On the other hand, if the annealing temperature exceeds 830°C, after completion of recrystallization, grain growth may progress, and a problem of insufficient strength may occur. On the other hand, although not particularly limited, from the viewpoint of further improving the above-mentioned effects, preferably, the lower limit of the annealing temperature may be 742°C, or the upper limit of the annealing temperature may be 810°C.
[0065] According to one aspect of the present invention, the method may include a step of cooling the annealed cold-rolled steel sheet and then directly galvanizing the steel sheet in a continuous hot-dip galvanizing line. That is, the method may include a step of immersing the annealed cold-rolled steel sheet in a zinc-based plating bath to galvanize the steel sheet. In the present invention, the zinc-based plating bath refers to a plating bath containing an excessive amount of zinc (i.e., 50% by weight or more to 100%). The composition of the zinc-based plating bath is not particularly limited, and may further contain Al or unavoidable impurities, and a plating bath commonly used in the art may be applied.
[0066] Thereafter, although not particularly limited, according to one aspect of the present invention, an alloying heat treatment can be selectively performed in the range of 500 to 560°C after the hot dip galvanizing. At this time, if the alloying heat treatment temperature is less than 500°C, the alloying does not proceed sufficiently, and if the alloying heat treatment temperature exceeds 560°C, the alloying proceeds excessively, causing the plating layer to become brittle, which may induce problems such as peeling of the plating due to processing such as pressing. On the other hand, although not particularly limited, from the viewpoint of further improving the above-mentioned effects, preferably, the lower limit of the alloying heat treatment temperature may be 520°C, or the upper limit of the alloying heat treatment temperature may be 545°C.
[0067] Meanwhile, according to one aspect of the present invention, the alloyed heat-treated steel sheet may further include, but is not limited to, a step of selectively temper rolling the steel sheet using a skin-pass roll having a roughness (Ra) of 1.0 to 1.6 μm. If the roughness (Ra) of the skin-pass roll during the temper rolling is less than 1.0 μm, it may be difficult to ensure the distinctness of image required to have a beautiful surface after painting. Also, if the roughness (Ra) of the skin-pass roll during the temper rolling is more than 1.6 μm, problems with pressability may occur.
[0068] According to one aspect of the present invention, the temper rolling step may be performed at a reduction of 0.6 to 1.2%. If the reduction in the temper rolling is less than 0.6%, problems may occur in shape correction, and if it exceeds 1.2%, problems may occur in which the yield strength becomes excessively high due to an increase in mobile dislocations. EXAMPLES
[0069] (Example) The present invention will be described in more detail below with reference to examples. However, it should be noted that the following examples are for illustrative purposes only and are not intended to limit the scope of the present invention. The scope of the present invention is determined by the matters described in the claims and matters that can be reasonably inferred therefrom.
[0070] (Experimental Example 1) A steel having an alloy composition shown in Table 1 below was continuously cast so as to satisfy the average casting speed and cooling water amount shown in Table 2 below to obtain a steel slab having a thickness of 250 mm, and the surface of the slab was then spalled to a thickness of 2 to 4 mm. The slab was reheated to 1250°C, and then hot-rolled, coiled, and cold-rolled under the conditions shown in Table 3 below to obtain a steel sheet having an average thickness of 0.85 mm. The steel sheet was then continuously annealed and immersed in a zinc-based plating bath containing, by weight, 0.121 to 0.133% Al, the balance Zn, and other unavoidable impurities, to perform alloyed hot-dip galvanizing to produce a plated steel sheet.
[0071] [Table 1]
[0072] [Table 2] Vc*: Average casting speed during continuous casting Wq*: Amount of cooling water during continuous casting
[0073] [Table 3] FDT*: Finish rolling temperature CT*: Winding temperature
[0074] For each of the plated steel sheets obtained from the above-mentioned invention examples 1 to 8 and comparative examples 1 to 4, the yield strength (YS), tensile strength (TS) and fracture elongation (T-El) were measured and are shown in Table 4 below. Specifically, after measuring the width, length of the parallel part and thickness of the test piece, the test piece was attached to a tensile tester and was waited until the test piece was broken, and then the yield strength, tensile strength and fracture elongation of the test piece were measured. The yield strength is the limit stress when elastic deformation occurs and is usually expressed as a value with a 0.2% offset, the tensile strength is the value obtained by dividing the maximum load by the circular cross section, and the fracture elongation is the deformation amount of the test piece after fracture from the tensile test expressed in %. At this time, a tensile strength of 390 MPa or more and an elongation of 28% or more were evaluated as passing.
[0075] Meanwhile, to evaluate the r-value, which is an index of deep drawing, JIS No. 5 tensile test pieces were taken from the galvannealed steel sheet in three directions: parallel to the rolling direction, at 45°, and perpendicular to the rolling direction, and the r-value of each test piece was measured. For example, the r-value can be measured by measuring the change in thickness and width at the point where a tensile deformation of about 15% has been performed in the above-mentioned tensile test, and determining the ratio of the change in width to the thickness. The r-value parallel to the rolling direction is then set as r0, and the r-value in the 45° direction is set as r 45 , the r value in the perpendicular direction is r 90 When the above formula is used, the r-value is calculated from the relation A using the r-values in each direction, and a specimen with an r-value of 1.2 or more is evaluated as passing.
[0076] [Equation A] r=r0+2*r 45 +r 90 / 4
[0077] In addition, surface linear defects were visually confirmed in the form of black lines, and the total number of linear defects per coil was confirmed on an SDD (Surface Defect Detector) and evaluated as "good" or "bad" according to the following criteria. Good: The number of linear defects on the SDD is 100 or less. Defects: More than 100 linear defects on the SDD
[0078] The Mo ratio "Mt / Ms" obtained from the above-mentioned Relational Formula 1 was measured using a GDS (Glow Discharge Spectrometer). Specifically, after removing the coating layer of the hot-dip galvanized test piece by pickling, the Mo content in the extreme surface layer of the base iron (i.e., a point 0.1 μm away from the surface of the base iron in the thickness direction) was measured by GDS, and the average Mo content (Mt) in the extreme surface layer was obtained. In addition, the base iron was polished from the surface to 1 / 4t in the thickness direction, and the Mo content in the surface layer of the base iron (i.e., a point 1 / 4t away from the surface of the base iron in the thickness direction; at this time, the t was 0.9 mm) was measured by GDS, and the average Mo content (Ms) in the surface layer was obtained. The Mo concentration ratio (i.e., Mt / Ms value) in the extreme surface layer and the surface layer of the base iron obtained in this way was measured and shown in Table 4 below.
[0079] In addition, the microstructures of the cut sections of the plated steel sheets in the thickness direction (i.e., the direction perpendicular to the rolling direction) were observed with an optical microscope (OM), and it was confirmed that the microstructures of the following Invention Examples 1 to 8 and Comparative Examples 1 to 6 contained 99% or more of ferrite. At this time, the average crystal grain size of the ferrite was measured and is shown in Table 4 below.
[0080] [Table 4] Mt*: Average weight percent content of Mo at a point 0.1 μm away from the surface of the base iron in the thickness direction of the base iron Ms*: Average weight percent of Mo at 1 / 4t from the surface of the base steel in the thickness direction of the base steel GS* (grain size): Average grain size of ferrite (average circular equivalent diameter) based on the cross section of the plated steel sheet in the thickness direction
[0081] As shown in Table 4 above, in the case of Invention Examples 1 to 8, which satisfy the alloy compositions and manufacturing conditions of the present invention, all of them satisfy Relational Formula 1, and the plating layer of each plated steel sheet was dissolved in a hydrochloric acid solution, and the dissolved liquid was analyzed by a wet analysis method (ICP) to measure the composition of the plating layer. As a result, it was confirmed that the plating layer was composed of, by weight%, 8 to 13% Fe, with the remainder being Zn and other impurities.
[0082] The plated steel sheets produced in the above invention examples 1 to 8 all had a tensile strength of 390 MPa or more, a yield strength of 205 MPa or more, and excellent strength characteristics, while also having an elongation of 28% or more and excellent formability. Furthermore, it was confirmed that the r-value was 1.2 or more, which indicated excellent deep drawability, and that surface linear defects were prevented.
[0083] In contrast, it was confirmed that Comparative Examples 1 to 6, which do not satisfy one or more of the alloy compositions and manufacturing conditions of the present invention, are inferior in one or more of the above-mentioned characteristics to Inventive Examples 1 to 8 of the present application.
[0084] In particular, a photograph of the surface of the plated steel sheet produced in the above-mentioned Example 1 observed by a scanning electron microscope (SEM) is shown in FIG. 1, and it was confirmed that the alloying proceeded uniformly. On the other hand, a photograph of the surface of the plated steel sheet produced in the above-mentioned Comparative Example 4 observed by a SEM is shown in FIG. 2, and it was confirmed that the alloying proceeded non-uniformly in Comparative Example 4. This is because in Comparative Example 4 which does not satisfy the relational formula 3 of the present application, the number of P-segregated sections increases, and alloying delay occurs in the P-segregated sections of the surface layer, and alloying proceeds non-uniformly. Also, unlike FIG. 1, in FIG. 2, recessed portions like grooves where alloying occurred non-uniformly were found, and it was confirmed that a black hue difference was induced when visually observed, resulting in poor surface quality in appearance.
[0085] (Experimental Example 2) The plated steel sheets obtained from Inventive Example 1 and Comparative Example 1 in Experimental Example 1 described above were further subjected to temper rolling using a skin pass roll having a roughness (Ra) under the conditions shown in Table 5 below.
[0086] [Table 5]
[0087] For each of the plated steel sheets obtained from the above-mentioned respective invention examples 1-1 to 1-4 and comparative example 1-1, the Mo ratio in relational formula 1, the surface roughness (Ra) of the plated layer, the area fraction of ferrite, and the size of ferrite crystal grains were measured and shown in the following Table 6. In addition, for the plated steel sheets obtained from the respective invention examples and comparative examples, evaluation was performed in the same manner as in the above-mentioned experimental example 1 and the results are shown in the following Table 6.
[0088] Furthermore, to evaluate image clarity, which is a scale showing the beauty of the finished product after painting, cupping was performed at a height of 17 mm, and waviness (Wsa) was measured in the rolling direction starting from the center. When measuring Wsa, a 225 mm x 225 mm blank was pressed with a presser having a hollow punch with a diameter of 75 mm and the force of the blank holder so that any material movement of the substrate was completely suppressed between the blank holder and the die to produce a cup. The deformation of the cup was adjusted so that the punch drawing depth was 17 to 18 mm and the thickness deformation rate of the bottom was 5% ± 0.2%. The Wsa value measured by the above method was evaluated as "good" when it was 0.35 μm or less, and "poor" otherwise, as shown in Table 6 below.
[0089] [Table 6]
[0090] As shown in Table 6, in the case of Examples 1-1 to 1-4 satisfying the alloy composition and manufacturing conditions of the present invention, the tensile strength was 390 MPa or more, the yield strength was 205 MPa or more, and it was confirmed that the strength characteristics were excellent, while the elongation was 28% or more and the formability was also excellent. Furthermore, the r value was 1.2 or more, and it was confirmed that the deep drawability was excellent and the surface linear defects were prevented.
[0091] In particular, among the above-mentioned invention examples, in the case of invention examples 1-1 and 1-2 in which the roughness (Ra) of the skin pass roll is in the range of 1.0 to 1.60 μm and the rolling reduction rate during temper rolling is in the range of 0.60 to 1.20%, it was confirmed that compared with invention examples 1-3 and 1-4, the examples have a beautiful surface after painting, are excellent in image clarity and pressability, and the yield strength also satisfies the range of 205 to 340 MPa.
[0092] On the other hand, in the case of Comparative Example 1-1, which does not satisfy the alloy composition of the present invention, the tensile strength is too high, the elongation is low, and the formability is poor. Since the r-value is less than 1.2, the deep drawability is poor and linear defects occur on the surface.
Claims
1. With bare iron, A plating layer formed on the base steel, The base iron contains, by weight, C: 0.003 to 0.009%, Si: 0.05% or less, Mn: 0.4 to 1.0%, P: 0.04 to 0.09%, S: 0.01% or less, N: 0.005% or less, S.Al: 0.1% or less, Mo: 0.03 to 0.08%, Ti: 0.005 to 0.03%, Nb: 0.02 to 0.045%, Cu: 0.06 to 0.15%, and B: 0.003% or less. The balance is Fe and other unavoidable impurities. A plated steel sheet satisfying the following relational expression 1. [Relationship 1] 1.6≦Mt / Ms≦6 (In the above-mentioned Relational Formula 1, the Mt represents the average content of Mo by weight at a point 0.1 μm away from the surface of the base iron in the thickness direction of the base iron side. The Ms indicates the average content of Mo by weight at a point 1 / 4t from the surface of the base iron in the thickness direction of the base iron side. The t indicates the total average thickness of the base iron and is in the range of 0.8 to 1 mm.
2. 2. The plated steel sheet according to claim 1, wherein the microstructure of the base steel contains, in terms of area fraction, 99% or more of ferrite, with the remainder being pearlite.
3. The plated steel sheet according to claim 2, wherein the average crystal grain size of the ferrite is 5 to 15 μm.
4. The tensile strength is 390 MPa or more, The plated steel sheet according to claim 1, wherein the elongation is 28 to 43%.
5. The plated steel sheet according to claim 4, having a yield strength of 205 MPa or more.
6. The plated steel sheet according to claim 1, wherein the plating layer contains, by weight percent, 8 to 13% Fe, the balance being Zn and other inevitable impurities.
7. The plated steel sheet according to claim 1 , which satisfies the following relational expression 2: [Relationship 2] [P] / [Mo]≦1.162 (In the above Relational Formula 2, [P] represents the average weight percent content of P in the base iron, and [Mo] represents the average weight percent content of Mo in the base iron.)
8. A step of continuously casting a steel containing, by weight, C: 0.003-0.009%, Si: 0.05% or less, Mn: 0.4-1.0%, P: 0.04-0.09%, S: 0.01% or less, N: 0.005% or less, S.Al: 0.1% or less, Mo: 0.03-0.08%, Ti: 0.005-0.03%, Nb: 0.02-0.045%, Cu: 0.06-0.15%, and B: 0.003% or less, with the balance being Fe and other unavoidable impurities; reheating the slab obtained by continuous casting; hot rolling the reheated slab to provide a hot rolled steel sheet; coiling the hot-rolled steel sheet; cold rolling the hot rolled steel sheet to obtain a cold rolled steel sheet; Annealing the cold rolled steel sheet; and immersing the annealed cold-rolled steel sheet in a zinc-based plating bath to obtain a hot-dip galvanized steel sheet. The continuous casting satisfies the following Relation 3, [Relationship 3] 1≦Vc≦5-[P] / [Mo] (In the Relational Formula 3, Vc represents an average casting speed during continuous casting, and is expressed in m / min. [P] represents an average P content in the slab in weight percent, and [Mo] represents an average Mo content in the slab in weight percent.) The plated steel sheet is With bare iron, A plating layer formed on the base steel, A method for producing a plated steel sheet, which satisfies the following relational expression 1: [Relationship 1] 1.6≦Mt / Ms≦6 (In the above-mentioned Relational Formula 1, the Mt represents the average content of Mo by weight at a point 0.1 μm away from the surface of the base iron in the thickness direction of the base iron side. The Ms indicates the average content of Mo by weight at a point 1 / 4t from the surface of the base iron in the thickness direction of the base iron side. The t indicates the total average thickness of the base iron and is in the range of 0.8 to 1 mm.
9. The temperature for reheating the slab is 1180 to 1230°C; The hot rolling temperature is 880 to 970°C, The coiling temperature of the hot-rolled steel sheet is 600 to 640°C. The reduction ratio during the cold rolling is 70 to 83%, The method for producing a plated steel sheet according to claim 8, wherein the temperature at which the cold-rolled steel sheet is annealed is 740 to 830°C.
10. The method for producing a plated steel sheet according to claim 8, wherein cooling is performed with a cooling water amount of 0.8 to 3.0 L / kg during the continuous casting.
11. A method for producing the plated steel sheet, comprising: The method further includes the step of performing an alloying heat treatment at a temperature in the range of 500 to 560° C. after the hot-dip galvanizing, The method for producing a plated steel sheet according to claim 8, further comprising the step of temper rolling the alloyed heat-treated steel sheet using a skin-pass roll having a roughness (Ra) of 1.0 to 1.6 μm.
12. The method for producing a plated steel sheet according to claim 11, wherein the temper rolling is performed at a rolling reduction of 0.6 to 1.2%.
13. The method for producing a plated steel sheet according to claim 8, further comprising the step of performing an alloying heat treatment at 500 to 560°C after the hot dip galvanizing step.
Citation Information
Patent Citations
Manufacture of galvannealed steel sheet excellent in formability
JP1993228501A
Method for manufacturing galvannealed steel sheet superior in formability
JP2004169160A
Method for producing high tensile strength cold rolled deep-drawing steel sheet excellent in surface property
JP2006342412A
Method for producing continuous-cast slab and high-tension hot rolled steel plate, high-tension cold rolled steel sheet, and high-tension galvanized steel sheet
JP2007216247A
Cold-rolled high-tensile-strength steel sheet, high-tensile-strength galvanized steel sheet, and manufacturing method therefor
JP2008214656A